2006
DOI: 10.1007/s11461-006-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host plant species on the development and reproduction of hawthorn spider mites

Abstract: A leaf disc bioassay was employed to investigate the influence of host species of deciduous fruit trees, like apple, peach, plum, cherry and apricot, on the development and reproduction of the hawthorn spider mite Tetranychus viennensis Zacher in the laboratory under conditions of 25±1℃, 60±10% RH and a photoperiod of 16 h: 8 h light: dark. This was done by determining the duration of each life stage of the mites, the intrinsic rate of population increase (r m ), mean generation time (T) and net reproductive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…The r m values on cherry and apple obtained in the present study were higher than those obtained by Li et al (2006). Similar to our finding, these authors also found that the r m of A. viennensis was higher on apple than on cherry; Gotoh and Takayama (1992) had not found this.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The r m values on cherry and apple obtained in the present study were higher than those obtained by Li et al (2006). Similar to our finding, these authors also found that the r m of A. viennensis was higher on apple than on cherry; Gotoh and Takayama (1992) had not found this.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our finding, these authors also found that the r m of A. viennensis was higher on apple than on cherry; Gotoh and Takayama (1992) had not found this. Li et al (2006) concluded that mites can adapt to the transferred host plant gradually, based on an initial adverse effect on development and reproduction of A. viennensis during a few generations after shifting host plants. Our results confirm their results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marcic (2003) reported effects of clofentezine on lifetable parameters of T. urticae females that survived a concentration causing ‡90% mortality at one of the developmental stages. However, clofentezine persists up to 12 weeks (Marshall et al 1994), during which at least three generations of T. viennensis (Li et al 2005) were exposed to the toxicants. One of the acknowledged limitations of conventional toxicity tests is their inability to evaluate the impact of toxicants on subsequent generations (Rebecca et al 2002).…”
Section: Introductionmentioning
confidence: 99%